Discussion of the Relative Information Content of Accruals and Cash Flows: Combined Evidence at the Earnings Announcement and Annual Report Release Date - O'Brien, Patricia C. (Journal of Accounting Research, 1986)
Patricia C. O'Brien, Discussion of the Relative Information Content of Accruals and Cash Flows: Combined Evidence at the Earnings Announcement and Annual Report Release Date, Journal of Accounting Research, Vol. 24, Studies on Alternative Measures of Accounting Income (1986), pp. 201-203